Effect of bioslurry on transplanted aus rice under rainfed condition in Sylhet (Bangladesh Journal of Agricultural Research, 2017)
An experiment was conducted in farmer’s field with the aim to evaluate the effect of integrated use of bioslurry and inorganic fertilizer on the agroeconomic performance of transplanted aus rice (t. aus) (cv. BRRIdhan42) in AEZ 20. The trial was laid out in a randomized complete block design with three replications. There were three treatments viz., T1: soil test based inorganic fertilizer dose for high yield goal (HYG), T2: cowdung (CD) slurry @ 5 t ha-1 with integrated plant nutrition system (IPNS) basis inorganic fertilizer dose for HYG and T3: Farmer’s practice (average of 20 farmers fertilizer dose). The highest mean grain yield (3.93 t ha-1) of t. aus rice was obtained from the treatment T2 followed by T1 (3.46 t ha-1). Gross return, gross margin and benefit cost ratio were also observed higher in T2. Therefore, fertilizer package NPKSZn @ 56-4-20-9-1 kg ha-1 + cow dung slurry @ 5 t ha-1 in IPNS approach might be helpful for getting higher grain yield of t. aus rice and maintaining sustainable soil health as well.Bangladesh J. Agril. Res. 42(3): 467-474, September 2017